The Influence of Organizational Culture and Organizational Communication on Job Satisfaction through Work Motivation as an Intervening Variable in Employees of the Padang Hilir District Office, Tebing Tinggi City - Sonya Sartika Simatupang; R Sabrina (Yayasan Multidimensi Kreatif, 2026)
This study aims to analyze the influence of organizational culture and organizational communication on job satisfaction through work motivation as an intervening variable in Padang Hilir District Office Employees, Tebing Tinggi City. The research uses a quantitative approach with an explanatory research method. Data collection was carried out through the distribution of questionnaires to employees, then analyzed using the Structural Equation Modeling method based on Partial Least Square (SEM-PLS). The results showed that the research model had a very strong predictive ability, as shown by the determination coefficient value (R-square) of 93.8% in the work motivation variable and 85.6% in the work satisfaction variable. Structural relationship testing showed that organizational culture had a positive and significant effect on work motivation with a path coefficient value of 0.521 and a p-value of 0.000, while organizational communication had a positive and significant effect on work motivation with a coefficient value of 0.458 and a p-value of 0.001. However, the effect of work motivation on job satisfaction has not shown statistical significance with a coefficient of 0.411 and a p-value of 0.064. The direct influence of organizational culture on job satisfaction has a coefficient of 0.087 with a p-value of 0.725, while organizational communication on job satisfaction has a coefficient of 0.440 with a p-value of 0.056. In addition, work motivation has not been proven to be a significant intervening variable, with the indirect influence of organizational culture on job satisfaction of 0.214 and organizational communication of 0.188. The findings of the study confirm that strengthening the organizational culture based on the values of ASN BerAKHLAK and improving the quality of internal communication are important factors in building motivation and supporting the improvement of employee job satisfaction.